Spatial autocorrelation and heterogeneity of fish resources in the Xijiang River, Pearl River Basin, China - Zhi, Wu; Shuli, Zhu; Jie, Li; Yuefei, Li; Yuguo, Xia; Xinhui, Li (Indian Journal of Fisheries, 2021)
The Xijiang River, China, is a hotspot for fish biodiversity. Using hydroacoustic data collected from March to June 2016, the spatial autocorrelation and heterogeneity of fish resources were determined using geostatistical methods. We analysed the skewness, kurtosis and coefficient of variation for fish density along the river and also examined the spatial autocorrelation of these data using Moranâ€™s I statistic. Fish density was low in most of the survey areas. Moranâ€™s I values were all positive (z>1.96, pâ‰¤0.01), which indicates significant spatial autocorrelation; however, the degree of spatial aggregation varied among months. Hotspot analysis revealed strong local spatial autocorrelation and varying â€œhotâ€ and â€œcold spotsâ€ in different months. The spatial heterogeneity and directional variation of fish densities were assessed using geostatistical methods and the best-fitting semivariogram was an exponential model. Spatial autocorrelation accounted for 56-75% of the variation in the model, which indicates that fish distribution in the Xijiang River has a clear spatial structure. The results show the applicability of acoustic methods to study the spatial autocorrelation and heterogeneity of fish resources in rivers and provide a reference for the management of fish stocks.Keywords: Fish resources; Hydroacoustic technology; Spatial autocorrelation; Variation characteristics; Xijiang River